The Analysis of Ecotourism Laws and Policies in Indonesia - R. Hendrik Nasution; Ricky Avenzora; Tutut Sunarminto (Media Konservasi, 2018)
This study aimed to analyze the chain posture, substantial content and time span of ecotourism laws and policies in Indonesia. The instrumentused in this research was closed ended questionare, which was then analyzed using One Score One Criteria System. In various criteria, the subtantialcontent of all ecotourism laws and policies in Indonesia showed a score of 5 or a rather good meaning. This non-optimal value can be said to have noclarity of comprehensive and structured objectives so that the dynamics of the substantial content in the law is still partial. Above that, it must beunderstood that ecotourism should not be interpreted as a journey to the natural in remote area only, but it must be enforced in every space oftourism destinations. Based on the research results on the legislation documents including (Laws, Government Regulations, Presidential Regulations,Presidential Decrees, Ministerial Regulations) it was found that between mandatory rules and implementing regulations were not set within a periodof about 2 years accordingly. Therefore, it is necessary for the integration of stakeholders to revise the various ecotourism laws and policies inIndonesia comprehensively, systematically and objectively so that in the dynamics of its implementation can optimize the seven pillars of ecotourismdevelopment.Keywords: analysis, criteria, law and policy